NFkB hyperactivation causes invasion of esophageal squamous cell carcinoma with EGFR overexpression and p120-catenin down-regulation - Lehman, Heather L. (Oncotarget, 2018)
Four out of five patients diagnosed with esophageal squamous cell carcinoma (ESCC) will die within five years. This is primarily a result of the aggressive invasive potential of the disease. Our research is focused on the interplay between tumor suppressors and oncogenes in the invasive process. Specifically, EGFR and p120-catenin (p120ctn) are commonly dysregulated genes that are indicative of poor prognosis in ESCC. In a previous study we demonstrated that in our 3D organotypic culture model, only when EGFR overexpression is combined with p120ctn inactivation do the cells transform and invade – as opposed to either event alone. The purpose of this present study was to identify the components of the molecular pathways downstream of p120ctn and EGFR that lead to invasion. Using both human esophageal keratinocytes and human ESCC cells, we have identified NFkB as a central regulator of the invasive process downstream of p120ctn down-regulation and EGFR overexpression. Interestingly, we found that NFkB is hyperactivated in cells with EGFR overexpression and p120ctn inactivation than with either EGFR or p120ctn alone. Inhibition of this NFkB hyperactivation results in complete loss of invasion, suggesting that NFkB signaling is necessary for invasion in this aggressive cell type. Furthermore, we have identified RhoA and Rho-kinase as upstream regulators of NFkB in this process. We believe the cooperation of p120ctn down-regulation and EGFR overexpression is not only important in the aggressive mechanisms of ESCC but could be broadly applicable to many other cancer types in which p120ctn and EGFR are involved.